Pengaruh Gaya Hidup Konsumen Terhadap Keputusan Membeli Perumahan CV. Nusantara Muara Teweh - Mtw, Mahmud (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2020)
This study aims to Want to see the magnitude of the influence of lifestyle on the decision to buy housing CV. NUSANTARA in Muara Teweh. Knowing the characteristics of consumers in the housing complex CV. NUSANTARA in Muara Teweh. This research method uses systematic observation and recording of the phenomenon being studied. This observation was conducted to obtain data on consumer behavior and variables that can influence it. The total respondents were 120 people. The results of data collection obtained that the lifestyle (activities, interests, and income) of consumers influence buying decisions in housing CV. NUSANTARA Muara Teweh. Prefers activities that involve many people, activities with neighbors, classic and elegant clothes that are the most dominant influence on consumers' decision to buy a house in housing CV. NUSANTARA based on the intention of the buyer. The results of the study concluded that lifestyle influences the decision to buy housing CV. NUSANTARA in Muara Teweh. The characteristics of consumers in the housing complex are like activities that involve people, activities with neighbors are not attractive, classic, and elegant clothing that most dominantly influences consumer decisions and buying a house in housing CV. NUSANTARA in Muara Teweh. For further researchers, developers are advised to add existing facilities and facilities. The existing facilities around the housing must be properly maintained so that they are not easily damaged, the developers pay attention to various marketing policies for their products, maximum service for the needs and desires of consumers.